Fragmentation reduces the importance of niche‐based factors relative to dispersal traits in structuring temperate forest understories. (14th November 2019) - Sonnier, Grégory; Johnson, Sarah E.; Waller, Donald M.
Abstract: Aim: The relative importance of stochastic and deterministic niche processes can affect the assembly of communities in response to land use context and change. In this study, we quantified the relative importance of dispersal‐ vs niche‐based processes in structuring forest plant metacommunities and sought to understand how these processes have changed in these forests over the past 50 years. Location: Wisconsin, USA. Methods: We used plant understorey community survey data in both the 1950s and 2000s from 142 upland forest stands in southern and northern Wisconsin forests to relate compositional similarity to geographic and environmental distances among sites (reflecting dispersal and niche‐based processes, respectively). We then partitioned the variance to determine their relative importance over time. Finally, we classified species into three dispersal groups based on seed mass, dispersal mode, and plant height to assess how these affect community structure. Results: Both niche and dispersal processes influence the structure of Wisconsin's forest plant understories. Niche‐based processes related to environmental differences among sites dominate the mostly continuous northern upland forests. In contrast, dispersal processes dominate community assembly in the more fragmented southern upland forests. Dispersal processes increased in importance in both regions and especially in more fragmented southern upland forests over the past 50 years. We detected no differences among dispersal groups in how similarity decays with geographic distance. Conclusions: In regions retaining heavy forest cover, niche‐based assembly still predominates while in areas with smaller scattered patches of forest, stochastic dispersal plays a greater role. Dispersal‐based processes increasingly dominate forest metacommunity dynamics in both regions. Abstract : We investigated community assembly in Wisconsin forests at two time periods (1950s and 2000s). Both environmental and dispersal processes influenced the assembly of these forests. However, dispersal limitation occurred more commonly in the fragmented southern upland forests than in the more continuous northern upland forests. The importance of dispersal limitation was higher in the 2000s than in the 1950s.